2014
DOI: 10.1039/c3cs60366k
|View full text |Cite
|
Sign up to set email alerts
|

Template effects and supramolecular control of photoreactions in solution

Abstract: A review of supramolecular and template effects on photochemical reactions in solution is presented. Photoinduced [2+2] and [4+4] cycloaddition reactions, isomerization, electron transfer and radical processes are covered, as well as examples of DNA photoligation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 271 publications
(329 reference statements)
0
62
0
Order By: Relevance
“…Since the short excited state lifetime and low activation energy for reaction in excited state leave little room for manipulating the chiral induction, to achieve enantioselectivity one has to ensure that the substrate molecule already resides in a chiral environment during the excitation step. Nevertheless, examples of excited state reactions with high enantioselectivity have been achieved (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Recently, a new strategy for high enantioselective photochemical reactions has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…Since the short excited state lifetime and low activation energy for reaction in excited state leave little room for manipulating the chiral induction, to achieve enantioselectivity one has to ensure that the substrate molecule already resides in a chiral environment during the excitation step. Nevertheless, examples of excited state reactions with high enantioselectivity have been achieved (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Recently, a new strategy for high enantioselective photochemical reactions has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was demonstrated that the optical properties of organic dyes may be modified drastically upon complexation in the CB cavity [7]. At the same time, this effect of the ligand–CB[ n ] interplay may be used to modify and control the photochemical properties of a guest molecule [89]. For instance, the encapsulation of photoactive molecules in the constrained medium of a cucurbituril cavity enables the performance of chemo-, regio- or stereoselective photoreactions that are not possible in homogeneous solution [1015].…”
Section: Introductionmentioning
confidence: 99%
“…8,16 Many reactions of cycloaddition are known in organic chemistry, for instance -[2 + 3] cyloaddition, 47 [3 + 4] cycloaddition, 48 [4 + 2] cycloaddition. Many examples of pre-organized dimeric pairs are described in the literature via the coordination of the initial ethylene systems with metal cations 11,30,32,34,38,40,43,50 or the formation of hydrogen bonds between the components, 7,9,10,12,14,15,17,20,21,[23][24][25]29,30,40,41,46,50 as well as entering two structural units in cavitand cavitycyclodextrins, calixarenes, cucurbit [8]uril, nanocages. Whereas, PCA represents a temperature independent process.…”
Section: Introductionmentioning
confidence: 99%
“…49 However, these reactions are thermal and they proceed in solution. 17,35,36,39,40 Another approach to create the "pre-organized" dimeric pair is only possible for the PCA reaction in the solid state. It is photochemically reversible, often regio-and stereoselective and it proceeds in both solution and in the solid phase.…”
Section: Introductionmentioning
confidence: 99%